(untitled) (Vietnam Journal of Community Medicine, 2026)
Background: Paroxysmal supraventricular tachycardia (PSVT) is a relatively common cardiac arrhythmia in clinical practice. Terminating a PSVT episode is crucial as it helps restore normal heart rhythm and prevents complications such as heart failure and cardiogenic shock, especially in emergency settings. Objective: To evaluate the results of treatment for terminating paroxysmal supraventricular tachycardia episodes in the Emergency Department of Nghe An General Friendship Hospital. Subjects and Methods: A cross-sectional descriptive study was conducted on 73 patients with PSVT at the Emergency Department of Nghe An General Friendship Hospital from January 2023 to June 2024. All patients received PSVT termination treatment according to protocol. Treatment effectiveness was assessed based on the restoration of normal sinus rhythm, hemodynamic improvement, resolution of clinical symptoms, and the absence of tachycardia recurrence. Results: Patients with PSVT presenting with subjective symptoms such as chest tightness/pain, palpitations, dyspnea, pounding heart, and syncope... Regarding PSVT termination, the success rates were lowest for vagal maneuvers (52.2%), followed by adenosine (66.7%), amiodarone (Cordarone) (91.3%), and electrical cardioversion (100%). Conclusion: Early detection, diagnosis, and treatment of PSVT in the Emergency Department have been shown to improve clinical outcomes by stabilizing the initial emergency condition. This also facilitates the process of referring patients for electrophysiological study and subsequent catheter ablation of the arrhythmia if indicated